The struck-off mystery. - Buntwal, N (1999)
Observations on ward rounds suggested that psychiatric patients might be at special risk of removal from their general practitioner's list. Little has been published on why patients are struck off and our first attempt at investigation was by direct appeals for patients. This drew a small and unsatisfactory sample. We then asked two family health services authorities to distribute questionnaires to struck-off patients. One agreed, but later withdrew cooperation. There is a danger that struck-off patients will become an underclass excluded from primary care. We propose anonymous collection of information by health authorities, so that policy can be reviewed if necessary.